2019
DOI: 10.1016/j.biopsych.2019.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological Phenotype in Angelman Syndrome Differs Between Genotypes

Abstract: BACKGROUND: Angelman syndrome (AS) is a severe neurodevelopmental disorder caused by either disruptions of the gene UBE3A or deletion of chromosome 15 at 15q11-q13, which encompasses UBE3A and several other genes, including GABRB3, GABRA5, GABRG3, encoding gamma-aminobutyric acid type A receptor subunits (b3, a5, g3). Individuals with deletions are generally more impaired than those with other genotypes, but the underlying pathophysiology remains largely unknown. Here, we used electroencephalography (EEG) to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
94
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 80 publications
(106 citation statements)
references
References 60 publications
(84 reference statements)
11
94
1
Order By: Relevance
“…EEG recordings were acquired in a clinical setting using an international 10-20 EEG montage (19 channels), and sleep EEG data were collected and marked by a technician as children slept naturally during the EEG session. Consistent with prior studies of AS [36][37][38][39]47 , qualitative inspection of EEG recordings revealed strongly abnormal EEG patterns in both sleep and wakefulness (see Fig. 1A,E for examples from a participant without seizures or medications).…”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…EEG recordings were acquired in a clinical setting using an international 10-20 EEG montage (19 channels), and sleep EEG data were collected and marked by a technician as children slept naturally during the EEG session. Consistent with prior studies of AS [36][37][38][39]47 , qualitative inspection of EEG recordings revealed strongly abnormal EEG patterns in both sleep and wakefulness (see Fig. 1A,E for examples from a participant without seizures or medications).…”
Section: Resultssupporting
confidence: 88%
“…Although our study found that delta power was indeed modulated by diminished consciousness (i.e., sleep) in AS, the effect sizes in both comparisons (d median = 0.60-0.74) were a fraction of that yielded by a prior comparison of delta power between TD control children and children with AS in the awake state (d = 1.22) 36 . Expressed as a percent change referenced to wakefulness, delta power increases when children with AS sleep by a maximum of 162% ( Fig.…”
Section: Discussioncontrasting
confidence: 81%
See 3 more Smart Citations